Application of Orem’s Self-Care Deficit theory and Nursing Support and giving education among patients with high blood pressure: Case study of Phrae Provincial Prison - Puntuwet, Kanittha (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
140 Journal of Phrae Public Health for Development (JPPHD) Vol.3 No.1 January - June 2023 Case study : Thai male patient, age 66 years, inmate in Phrae Province Prison; admitted to be taken into care as a case study on January 3, 2023. The patient had a headache in the occipital area for about 1 month, was worried and had insomnia symptoms. The patient has a chronic disease of high blood pressure. Results : The researchers therefore used a supportive educative system in patient care. The role of nurses is to educate and support patients in developing their ability to continuously care for themselves. The patient’s role includes: Determine all self-care needs. Self-care actions. The researcher followed up and evaluated the results of patient care. It was found that the patients to adjust their self-care appropriately to their environment in Phrae Province Prison. and there were no complications that occurred to the patient and this leads to maintain the well-being of life.